2020
DOI: 10.1103/physrevb.101.035151
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Cu3d multiplet structure in models of high- Tc cuprates

Abstract: We revisit the problem of the spectra of two holes in a CuO2 layer, modeled as a Cu-d 8 impurity with full multiplet structure coupled to a full O-2p band as an approximation to the local electronic structure of a hole doped cuprate. Unlike previous studies that treated the O band as a featureless bath, we describe it with a realistic tight binding model. While our results are in qualitative agreement with previous work, we find considerable quantitative changes when using the proper O-2p band structure. We al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…It also means pairing symmetry of Ba214 may carry admixtures from more than one gap, and the system becomes more three-dimensional. It renders this new HTS cuprate a multi-band system like the iron-based superconductors [36][37][38]. K. Liu et al suggested that the AFM fluctuations in onedimensional Cu-O chains may play an important role in the superconducting pairing of electrons [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also means pairing symmetry of Ba214 may carry admixtures from more than one gap, and the system becomes more three-dimensional. It renders this new HTS cuprate a multi-band system like the iron-based superconductors [36][37][38]. K. Liu et al suggested that the AFM fluctuations in onedimensional Cu-O chains may play an important role in the superconducting pairing of electrons [36].…”
Section: Resultsmentioning
confidence: 99%
“…T. Maier et al found two domes of pairing strength while one corresponds to the extremely overdoped regime and there is significant pairing strength in both the d-wave and s ± channels in the overdoped regime [37]. M. Jiang et al provided a new model featuring in a Cu-3d multiplet structure that only the ligand O-2p orbitals play an essential role [38].…”
Section: Resultsmentioning
confidence: 99%
“…most relevant hopping and Coulomb interactions within this set of orbitals. More recently, the role of the Cu 3d multiplet structure on the hole doped ground state is also studied [42]. While this model explains certain experimental observations, there is still a huge debate on what is the minimum model to describe the low-energy physics of doped cuprates.…”
Section: Multireference Perturbation Theorymentioning
confidence: 99%
“…We note that the four configurations shown in Table III encompass almost 90% of the d 8 wavefunction (with CAS-2 active space) in CaCuO 2 . Thus, the use of a three-band Hubbard model [41,42] to investigate the role of doped holes in CuO 2 planes is a reasonable A more intuitive and visual understanding of the distribution of the additional hole can be obtained by plotting the difference of the d 8 and the d 9 ground state electron densities as shown in Fig. 3.…”
Section: Wavefunction Of the Electron-removal D 8 Ground Statementioning
confidence: 99%
“…For example, in the holedoped case, the spins giving rise to the spin-fluctuation interaction are located on the Cu sublattice, while the paired holes are moving on the O p x/y sublattice. This situation can produce a different physical picture than if the interaction and the pairs both originate from the same orbital on the same lattice [9][10][11][12][13] . And indeed, studies have observed two-particle behavior in a two sublattice system that is not observed in a one-lattice system 14 .…”
Section: Introductionmentioning
confidence: 99%